2022
DOI: 10.1186/s40792-022-01485-8
|View full text |Cite
|
Sign up to set email alerts
|

Refractory postoperative Staphylococcus hominis bacteremia in a patient with an ACTH-producing pancreatic neuroendocrine neoplasm: a case report

Abstract: Background Staphylococcus hominis (S. hominis) is an opportunistic pathogen that is often highly resistant to antibiotics and is difficult to treat. In patients diagnosed with an adrenocorticotropic hormone (ACTH)-producing tumor that compromises the immune system due to hypercortisolemia, cancer treatment and infection control should be considered simultaneously. This report presents a case of refractory postoperative S. hominis bacteremia requiring the prolonged administration of several anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaén‐Luchoro et al, 2020 ), Dermabacter jinjuensis (Cho et al, 2018 ), Dermacoccus nishinomiyaensis (Joron et al, 2019 ; Ogbac, 2021 ), Enterococcus faecalis (Li et al, 2020 ), Rhodococcus corynebacterioides (Kitamura et al, 2012 ), Brachybacterium paraconglomeratum (Murata et al, 2020 ), Streptococcus agalactiae (Ya'qoub et al, 2018 ), Micrococcus luteus (Zhu et al, 2021 ) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017 ; Jeon et al, 2022 ; Muraki et al, 2022 ; Uddin et al, 2022 ; Vasconcellos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaén‐Luchoro et al, 2020 ), Dermabacter jinjuensis (Cho et al, 2018 ), Dermacoccus nishinomiyaensis (Joron et al, 2019 ; Ogbac, 2021 ), Enterococcus faecalis (Li et al, 2020 ), Rhodococcus corynebacterioides (Kitamura et al, 2012 ), Brachybacterium paraconglomeratum (Murata et al, 2020 ), Streptococcus agalactiae (Ya'qoub et al, 2018 ), Micrococcus luteus (Zhu et al, 2021 ) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017 ; Jeon et al, 2022 ; Muraki et al, 2022 ; Uddin et al, 2022 ; Vasconcellos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dermabacter jinjuensis (Cho et al, 2018), Dermacoccus nishinomiyaensis (Joron et al, 2019;Ogbac, 2021), Enterococcus faecalis (Li et al, 2020), Rhodococcus corynebacterioides (Kitamura et al, 2012), Brachybacterium paraconglomeratum (Murata et al, 2020), Streptococcus agalactiae (Ya'qoub et al, 2018), Micrococcus luteus (Zhu et al, 2021) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022;Uddin et al, 2022;Vasconcellos et al, 2022).…”
Section: Air Sampling Protocols and Bacterial Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaen-Luchoro et al, 2020), Dermabacter jinjuensis (Cho et al, 2018), Dermacoccus nishinomiyaensis (Joron et al, 2019;Ogbac, 2021), Enterococcus faecalis (Li et al, 2020), Rhodococcus corynebacterioides (Kitamura et al, 2012), Brachybacterium paraconglomeratum (Murata et al, 2020), Streptococcus agalactiae (Yaqoub et al, 2018), Micrococcus luteus (Zhu et al, 2021) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022, Uddin et al, 2022Vasconcellos et al, 2022).…”
Section: Air Sampling Protocols and Bacterial Identificationmentioning
confidence: 99%
“…Conversely, S. hominis has been reported as an opportunistic pathogenic bacterium typically found in the human oropharynx and URT (Otto, 2010;Szczuka et al, 2018); present in the blood of immunocompromised patients with bacteremia, septicemia, endophthalmitis, and endocarditis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022, Uddin et al, 2022Vasconcellos et al, 2022), and often it can form biofilms on medical devices (Villarreal-Salazar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%